PERLINDUNGAN HAK WARIS ANAK HASIL PERKAWINAN SIRI MENURUT KOMPILASI HUKUM ISLAM DAN HUKUM POSITIF INDONESIA - Alfaiza, Zahroul Firdausi; Wibowo, Muhammad Kurniawan Budi; Baehaqi, B (AL HUKMU: Journal of Islamic Law and Economics, 2024)
The main problem in siri marriages in general is related to the rights of a wife who cannot claim a share of property from her husband and the rights of a child who is born becomes obstructed and is not entitled to inherit property from the father, because he has a weak position in the eyes of the law. This research was conducted with the aim of knowing the legal protection and inheritance rights for children of siri marriages. This study uses a literature/library research method with a normative juridical approach and a normative theological approach. Data collection was carried out using the library method, namely the method of searching, collecting and analyzing data sources which were processed and displayed in the form of library research. The results of the study show that children of siri marriages have the same position as legitimate children in the eyes of Islamic law and Indonesian law. But there are two different things, namely the issue of identity and inheritance. Islamic law places the status of children from siri marriages on a par with legitimate children even though they are not legalized. Meanwhile, in the view of Indonesian law, children from siri marriages can have the same status and share of inheritance as legitimate children, provided that the child has been legalized through the marriage certificate of his parents. In both of these legal views, an existing marriage must obtain a marriage certificate from the Marriage Registration Officer (PPN), so that without registration in the child's identity, the child is considered a child out of wedlock.